Physical Expansion of Layered Graphene Oxide Nanosheets by Chemical Vapor Deposition of Metal–Organic Frameworks and their Thermal Conversion into Nitrogen‐Doped Porous Carbons for Supercapacitor Applications. Issue 6 (28th August 2019) - Amer, Wael A.; Wang, Jie; Ding, Bing; Li, Tao; Allah, Abeer Enaiet; Zakaria, Mohamed B.; Henzie, Joel; Yamauchi, Yusuke
Abstract: Graphene oxide (GO) nanosheets show good electrical conductivity and corrosion resistance in electrochemical devices. However, strong van der Waals attraction between adjacent nanosheets causes GO materials to collapse, reducing the exposed surfaces and limiting electron/ion transport in porous electrodes. GO nanosheets mixed with Zn5 (OH)8 (NO3 )2 ⋅2 H2 O (ZnON) nanoplates create a layered composite structure. Exposing the resultant GO/ZnON to 2‐methylimidazole vapor leads to the conversion of ZnON into the zeolitic imidazolate framework ZIF‐8. The transformation of ZnON into ZIF‐8 leads to a huge physical expansion of the interlayer space between the GO sheets. Annealing the material at high temperature caused the ZIF‐8 to be converted into highly porous nitrogen‐doped carbon, but the GO nanosheets maintained a large separation and high surface area. The morphology and porous structure of the post‐annealing carbon material was sensitive to the initial ratio of ZnON to GO. The optimized sample exhibited several favorable features, including a large surface area, high degree of graphitization, and a high amount of nitrogen doping. Using chemical vapor deposition of metal–organic frameworks to physically expand nanomaterials is a novel method to increase the surface area and porosity of materials. It enabled the synthesis of nanoporous carbon electrodes with high capacitance, good rate capability, and long cyclic stability in supercapacitor devices. Abstract : Vapor expansion and GO ! A layered GO/ZIF‐8 composite is prepared by transforming Zn5 (OH)8 (NO3 )2 ⋅2 H2 O (ZnON) nanoplates to ZIF‐8 through a chemical vapor deposition approach using 2‐methylimidazole (2‐MeIm) vapor. The ZIF‐8 are directly carbonized on the surface of GO, forming rGO/ZIF‐8‐derived nitrogen‐doped porous carbons.